La discalculia y su incidencia en el aprendizaje algebraico, en estudiantes de octavo año, Unidad Educativa “Atahualpa”, Machala, 2024 - 2025. - Pauta Otorongo, Mirella Lisseth; Alvarado Angel, Maybe Estefania (Machala: Universidad Técnica de Machala, 2025)
This capstone project addresses the issue of dyscalculia and its impact on the learning of algebraic processes among eighth grade students at the “Atahualpa” Educational Unit in the city of Machala during the 2024–2025 school year. The research originated from observations of multiple difficulties students face when interpreting mathematical symbols, solving algebraic operations, applying rules, and comprehending abstract concepts inherent to algebra—especially those with specific learning disorders such as dyscalculia.The study was conducted using a mixed-methods approach with explanatory, descriptive, relational, and propositional levels. This design enabled an understanding of the root causes of the problem, a description of its impact in the classroom, an analysis of the correlations among involved variables, and the proposal of methodological alternatives to address it. The methodology combined documentary and fieldwork approaches: reviewing academic literature and collecting data through surveys administered to both teachers and students, along with direct observations.Findings revealed that dyscalculia significantly impairs algebra performance by undermining comprehension of mathematical symbols, mastery of operational rules, and logical structuring of exercises. Additionally, the study identified a limited level of teacher preparation in recognizing and addressing this difficulty, as well as scarce implementation of adaptive strategies and inclusive pedagogical resources in classrooms.The study concludes that it is essential to implement specific curricular adaptations, incorporate playful learning activities, and promote an inclusive education framework that responds to the real needs of students with dyscalculia.
El presente trabajo de titulación aborda la problemática de la discalculia y su impacto en el aprendizaje de los procesos algebraicos en estudiantes de Octavo año de la Unidad Educativa “Atahualpa” de la cuidad de Machala durante el período lectivo 2024- 2025. La investigación surge a partir de la observación de múltiples dificultades que enfrentan los estudiantes al momento de interpretar símbolos matemáticos, resolver operaciones algebraicas, aplicar reglar y comprender conceptos abstractos propios del álgebra, especialmente en aquellos que presentan trastornos específicos del aprendizaje como la discalculia. El estudio se desarrolló bajo un enfoque mixto, con un nivel explicativo, descriptivo, relacional y propositivo, lo que permitió comprender las causas del problema, describir su impacto en el aula, establecer la correlación entre variables involucradas y plantear alternativas metodológicas para su abordaje. La modalidad fue documental y de campo, con revisión de literatura académica y recolección de datos a través de encuestas aplicadas a docentes y estudiantes, así como observaciones directas. Los resultados evidenciaron que la discalculia afecta de manera significativa el desempeño en el álgebra, infiriendo en la comprensión de signos matemáticos, el uso de reglas operativas y la estructuración lógica de los ejercicios. Asimismo, se identificó que existe una limitada preparación docente en el reconocimiento y tratamiento de esta dificultad, así como una escasa implementación de estrategias adaptativas y recursos pedagógicos inclusivos en las aulas. El estudio concluye que es imprescindible implementar adaptaciones curriculares específicas, incorporar actividades lúdicas y fomentar una educación inclusiva que responda a las necesidades reales del estudiante con discalculia.
Keywords: DISCALCULIA; PROCESOS ALGEBRAICOS; DIFICULTADES DE APRENDIZAJE; EDUCACIÓN INCLUSIVA; ADAPTACIONES CURRICULARES